Monetary and Exchange Rate Dynamics During Disinflation : An Empirical Analysis - Zhang, Lei (IMF Working Papers; Working Paper ;, 2005)
Based on the observed behavior of monetary aggregates and exchange rates, we classify inflation-stabilization episodes into two categories: de facto exchange rate-based stabilizations (ERBS) and non-ERBS. Unlike the standard de jure ERBS studied in the literature, de facto ERBS encompass cases in which the central bank intervenes in the foreign exchange market but does not preannounce the use of an exchange rate anchor. The number of the de facto ERBS is twice as large as that of de jure ERBS. Output dynamics during disinflation do not differ significantly between these two groups. We conclude that empirical studies on the effects of exchange rate anchors must seek to disentangle the effects of their announcement from those related to their role in the remonetization process.